1900 Ga. Laws 201, § 15 - (:unkn) unknown (General Publisher, 1900)
Granted the town council to regulate the keeping and selling of dynamite, gunpowder, kerosene, and all other hazardous articles of merchandise.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER